Conceptualisation, development and validation of green marketing orientation (GMO) of SMEs in India: a case of electric sector. Issue 2 (19th August 2014) - Chahal, Hardeep; Dangwal, Ramesh; Raina, Swati; Jones, Grant; Jones, Grant
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of the study is twofold. First, to examine the domain of green marketing construct in context to Small and Medium Enterprises (SMEs) operating in emerging economies (i.e. India) across electrical industries and second, to assess its impact on the SMEs performance. Design/methodology/approach All the owners of electrical industries (SMEs) operating in Jammu District that is, 152 were contacted using census method. Findings The study identifies and confirms five factors namely greening the process, green supply chain management, green strategic policy initiative, proactive energy conservation and green innovation of green marketing as important dimensions of GMO scale. All the dimensions of GMO scale have positive and significant impact on performance of the firms. Also there exists stronger impact of green marketing dimensions on the customer (B2B) satisfaction and employee retention. Research limitations/implications The research has certain unavoidable limitations. First, the study is based on only one sector that is, electrical industries operating in developing industrial region of India and hence future research is suggested to comprehend green marketing in other green-savvy manufacturing sectors like pharmaceutical sector and service sector like hotels and hospitals. Further, the study has focused on the development of GMO scale and future studies need to extend research to include variables like green satisfaction, green trust and green loyalty to understand their mediating role in green marketing and performance relationship. Furthermore, the moderating role of variables such as nature and age of the SMEs can also be studied in future research. Practical implications Green Marketing Orientation (GMO) allows managers to understand how their firms facilitate green environment and they affect the business outcomes. Furthermore, GMO takes into consideration all important aspects (greening the process, green supply chain management, green strategic policy initiatives, proactive energy conservation and green promotion) which provide better explanatory power and identification of priority areas for managerial attention. GMO can be used by managers to determine which strategies and practices will have the most positive influence on employees' outcome. Originality/value This paper can help managers in identifying the perspectives of GMO (green marketing orientation) in electrical sector for the developing countries. Unlike the three dimensions confirmed by studies, this study established five dimensions of green marketing namely, greening the process green supply chain management, green strategic policy initiatives, proactive energy conservation and green promotion.